PRİMARY CONJUNCTIVAL LYMPHOMA, 2 CASES - Günay Süleymanlı; Yasemin Aydınalp Camadan; Tuğba Toyran; Berksoy Şahin (Hematology, Transfusion and Cell Therapy)
Introduction: Extranodal marginal zone lymphoma (EMZL) is the most common subtype of conjunctival lymphoma. Management of conjunctival lymphoma consists of radiotherapy, surgery, chemotherapy, antibiotics and targeted therapies (Anti-CD 20) based on case series and retrospective studies. Appropriate treatment should be chosen based on the type of lymphoma, extent of spread, and patient-specific factors. We present two patients with localized disease diagnosed with primary conjunctival EZML by biopsy, for whom we planned different treatment plans. Case Reports: Case 1: A 64-year-old female patient presented with a pink-red mass on the lateral conjunctiva of her right eye. (Fig. 1A) Conjunctival biopsy was reported as Non-Hodgkin lymphoma, EMZL.(CD 20(+) and Ki-67 3-4%) No extraocular involvement on PET/CT. Orbital MRI showed a 2.5 cm soft tissue lesion surrounding the right globe laterally and posteriorly. The patient started rituximab and bendamustine treatment, and the lesion in the right orbit was not observed in the current follow-up imaging after 3 cycles of treatment. (Fig. 1B) The patient continued with rituximab and bendamustine treatment.Case 2: When the 52-year-old female patient first appeared two years ago, a conjunctival biopsy revealed that she had EMZL. Radiotherapy was recommended for her localized disease, but she declined it. She received eight cycles of rituximab treatment and was monitored in remission. One year later, salmon-colored lesions were found in the inner corner of both eyes. EZML was also found in the new biopsy. There was no ocular involvement. The patient received 6 cycles of rituximab bendamustine and maintenance rituximab for recurrent and bilateral lesions. We are currently monitoring the patient and the disease is in complete remission. Discussion: Lymphoma is one of the most frequently occurring malignant tumors of the conjunctiva. In patients with lesions that like a ''salmon patch'' and unexplained chronic follicular conjunctivitis, lymphoma should be suspected.